Aspects of motivating and motivating employees in the organization (Texas Journal of Multidisciplinary Studies, 2022)
Development of scientifically based proposals and recommendations for improving socioeconomic mechanisms for enhancing employee motivation in the context of the modern transition to an innovative economy. The article proposes ways to identify increased motivation of employees at the enterprises of the Association "Uzbekyengilsanoat", to improve the methods of satisfaction of labor motivation